PERBEDAAN PENAFSIRAN AYAT TENTANG IJBAR DAN IMPLEMENTASINYA DALAM KONTEKS KEKINIAN - Bilqis Nadya Tillah; Muzammil Imron; Moh Hasyim Abdul Qadir (Mozaic: Islamic Studies Journal, 2022)
Marriage by religion is recommended for those who are able to do so. Getting married is said to be able to provide peace of mind for married couples who love each other and love each other for the sake of Allah SWT. In order to reach the peak of love and love for Allah SWT. Many young people understand that marriage cannot be done because it is forced by anyone, but in many literatures it is explained that a mujbir guardian (father and grandfather) can force his daughter to marry, this concept is called Ijbar. Therefore, the author is interested in describing how the actual concept of coercion is meant and how it is implemented in the present context. Basically the concept of Ijbar boils down to a sense of responsibility and concern for parents for their children, Ijbar cannot be done arbitrarily without a sense of responsibility.